Narrative productions as feminist research methodology in Critical Social Psychology: Tensions and challenges - Lelya Troncoso Perez; Universidad de Chile; Caterine Galaz Valderrama; Universidad de Chile; Catalina Alvarez (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2017)
In this article, we discuss the relationship between critical perspectives in social psychology and feminist theories, considering two research experiences with feminist epistemologies and methodologies. Both investigations used narrative productions as a research method and an intersectional gender perspective, emerging from this crosses, tensions and methodological challenges transversal to both disciplines. Tensions guiding our empirical discussion regards to the complex relation between the corporeal and discursive dimensions in the production of knowledge; the problematization of power relations between researchers and the researched when attempting to construct horizontal relationships; and the tension between the practice of interpellation and making uncomfortable feminist critiques. Finally, we propose that the relation between feminist theorizations and critical social psychology facilitates the emergence of new political and theoretical potentials in social research, giving us clues in order to overcome dichotomous, hierarchical and depoliticized visions of social reality still present in classical and hegemonic social psychologies.